Can habitat modification in the native range promote invasion? - Arnaud Estoup; Philip E. Hulme; Kathryn A. Hodgins; Mathieu Gautier; Eric Lombaert; Manpreet K. Dhami; Angela McGaughran; Ruth A. Hufbauer (Trends in Ecology & Evolution, 2026)

The harlequin ladybird, Harmonia axyridis: global perspectives on invasion history and ecology - Helen E. Roy; Peter M. J. Brown; Tim Adriaens; Nick Berkvens; Isabel Borges; Susana Clusella-Trullas; Richard F. Comont; Patrick De Clercq; Rene Eschen; Arnaud Estoup; Edward W. Evans; Benoit Facon; et al. (Biological Invasions, 2016)

Invasion genetics of a human commensal rodent: the black rat R attus rattus in M adagascar - C. Brouat; C. Tollenaere; A. Estoup; A. Loiseau; S. Sommer; R. Soanandrasana; L. Rahalison; M. Rajerison; S. Piry; S. M. Goodman; J.‐M. Duplantier (Molecular Ecology, 2014)
Studies focusing on geographical genetic patterns of commensal species and on human history complement each other and provide proxies to trace common colonization events. On Madagascar, the unintentional introduction and spread of the commensal species R attus rattus by people may have left a living clue of human colonization patterns and history. In this study, we addressed this question by characterizing the genetic structure of natural populations of R . rattus using both microsatellites and mitochondrial sequences, on an extensive sampling across the island. Such data sets were analysed by a combination of methods using population genetics, phylogeography and approximate B ayesian computation. Our results indicated two introduction events to M adagascar from the same ancestral source of R . rattus , one in the extreme north of the island and the other further south. The latter was the source of a large spatial expansion, which may have initially started from an original point located on the southern coast. The inferred timing of introduction events—several centuries ago—is temporally congruent with the A rabian trade network in the I ndian O cean, which was flourishing from the middle of the first millennium.

Current distribution and population dynamics of the little fire ant supercolony in Cameroon - M. Tindo; P. S. Mbenoun Masse; M. Kenne; R. Mony; J. Orivel; A. Doumtsop Fotio; A. Fotso Kuaté; C. Djiéto-Lordon; A. Fomena; A. Estoup; A. Dejean; J. Foucaud (Insectes Sociaux, 2012)

Ecological genetics of invasive alien species - L.-J. Lawson Handley; A. Estoup; D. M. Evans; C. E. Thomas; E. Lombaert; B. Facon; A. Aebi; H. E. Roy (BioControl, 2011)

In defence of model-based inference in phylogeography - MARK A. BEAUMONT; RASMUS NIELSEN; CHRISTIAN ROBERT; JODY HEY; OSCAR GAGGIOTTI; LACEY KNOWLES; ARNAUD ESTOUP; MAHESH PANCHAL; JUKKA CORANDER; MIKE HICKERSON; SCOTT A. SISSON; NELSON FAGUNDES; et al. (Molecular Ecology, 2010)

Spatial genetic structure of a small rodent in a heterogeneous landscape - B. GAUFFRE; A. ESTOUP; V. BRETAGNOLLE; J. F. COSSON (Molecular Ecology, 2008)
Gene flow in natural populations may be strongly influenced by landscape features. The integration of landscape characteristics in population genetic studies may thus improve our understanding of population functioning. In this study, we investigated the population genetic structure and gene flow pattern for the common vole, Microtus arvalis , in a heterogeneous landscape characterised by strong spatial and temporal variation. The studied area is an intensive agricultural zone of approximately 500 km 2 crossed by a motorway. We used individual‐based Bayesian methods to define the number of population units and their spatial borders without prior delimitation of such units. Unexpectedly, we determined a single genetic unit that covered the entire area studied. In particular, the motorway considered as a likely barrier to dispersal was not associated with any spatial genetic discontinuity. Using computer simulations, we demonstrated that recent anthropogenic barriers to effective dispersal are difficult to detect through analysis of genetic variation for species with large effective population sizes. We observed a slight, but significant, pattern of isolation by distance over the whole study site. Spatial autocorrelation analyses detected genetic structuring on a local scale, most probably due to the social organisation of the study species. Overall, our analysis suggests intense small‐scale dispersal associated with a large effective population size. High dispersal rates may be imposed by the strong spatio‐temporal heterogeneity of habitat quality, which characterises intensive agroecosystems.

Invasion of Europe by the western corn rootworm, Diabrotica virgifera virgifera : multiple transatlantic introductions with various reductions of genetic diversity - M. CIOSI; N. J. MILLER; K. S. KIM; R. GIORDANO; A. ESTOUP; T. GUILLEMAUD (Molecular Ecology, 2008)
The early stages of invasion involve demographic bottlenecks that may result in lower genetic variation in introduced populations as compared to source population/s. Low genetic variability may decrease the adaptive potential of such populations in their new environments. Previous population genetic studies of invasive species have reported varying levels of losses of genetic variability in comparisons of source and invasive populations. However, intraspecific comparisons are required to assess more thoroughly the repeatability of genetic consequences of colonization events. Descriptions of invasive species for which multiple introductions from a single source population have been demonstrated may be particularly informative. The western corn rootworm (WCR), Diabrotica virgifera virgifera , native to North America and invasive in Europe, offers us an opportunity to analyse multiple introduction events within a single species. We investigated within‐ and between‐population variation at eight microsatellite markers in WCR in North America and Europe to investigate the routes by which WCR was introduced into Europe, and to assess the effect of introduction events on genetic variation. We detected five independent introduction events from the northern USA into Europe. The diversity loss following these introductions differed considerably between events, suggesting substantial variation in introduction, foundation and/or establishment conditions. Genetic variability at evolutionarily neutral loci does not seem to underlie the invasive success of WCR in Europe. We also showed that the introduction of WCR into Europe resulted in the redistribution of genetic variance from the intra‐ to the interpopulational level contrary to most examples of multiple introductions.

Do outbreaks affect genetic population structure? A worldwide survey in Locusta migratoria , a pest plagued by microsatellite null alleles - M‐P. CHAPUIS; M. LECOQ; Y. MICHALAKIS; A. LOISEAU; G. A. SWORD; S. PIRY; A. ESTOUP (Molecular Ecology, 2008)
An understanding of the role of factors intrinsic to a species’ life history in structuring contemporary genetic variation is a fundamental, but understudied, aspect of evolutionary biology. Here, we assessed the influence of the propensity to outbreak in shaping worldwide genetic variation in Locusta migratoria , a cosmopolitan pest well known for its expression of density‐dependent phase polyphenism. We scored 14 microsatellites in nine subspecies from 25 populations distributed over most of the species’ range in regions that vary in the historical frequency and extent of their outbreaks. We rejected the hypothesis that L. migratoria consists of two genetically distinct clusters adapted to habitats either rarely (nonoutbreaking) or cyclically (outbreaking) favourable to increases in population density. We also invalidated the current subspecific taxonomic classification based on morphometrics. Bayesian inferences indicated evidence of a homogenizing effect of outbreaks on L. migratoria population structure. Geographical and ecological barriers to gene flow in conjunction with historical events can also explain the observed patterns. By systematically assessing the effects of null alleles using computer simulations, we also provide a template for the analysis of microsatellite data sets characterized by a high prevalence of null alleles.

Introduction history of Drosophila subobscura in the New World: a microsatellite‐based survey using ABC methods - M. PASCUAL; M. P. CHAPUIS; F. MESTRES; J. BALANYÀ; R. B. HUEY; G. W. GILCHRIST; L. SERRA; A. ESTOUP (Molecular Ecology, 2007)
Drosophila subobscura is a Palearctic species that was first observed in South and North America in the early 1980s, and that rapidly invaded broad latitudinal ranges on both continents. To trace the source and history of this invasion, we obtained genotypic data on nine microsatellite loci from two South American, two North American and five European populations of D. subobscura. We analysed these data with traditional statistics as well as with an approximate Bayesian computation (ABC) framework. ABC methods yielded the strongest support for the scenario involving a serial introduction with founder events from Europe into South America, and then from South America into North America. Stable effective population size of the source population was very large (around one million individuals), and the propagule size was notably smaller for the introduction into South America (i.e. high bottleneck severity index with only a few effective founders) but considerably larger for the subsequent introduction into North America (i.e. low bottleneck severity index with around 100–150 effective founders). Finally, the Mediterranean region of Europe (and most likely Barcelona from the localities so far analysed) is proposed as the source of the New World flies, based on mean individual assignment statistics.

Strong population structure in the marine sponge Crambe crambe (Poecilosclerida) as revealed by microsatellite markers - S. Duran; M. Pascual; A. Estoup; X. Turon (Molecular Ecology, 2004)
Different categories of molecular markers have been used so far to study the population structure of sponges. However, these markers often did not have the resolution power to address precisely questions on structuring processes, especially at the intrapopulational level. In this study we show that microsatellites fulfil these expectations, allowing a fine description of population structure at different geographical scales in the marine sponge Crambe crambe . Specimens were collected in 11 locations, representing most of the Atlanto‐Mediterranean range of the species, and were analysed at six loci. As expected for a sessile invertebrate with lecitotrophic larvae, high levels of between‐population structure were found ( F ST = 0.18) and a significant isolation‐by‐distance pattern was observed. A strong genetic structure was also found within sampled sites ( F IS = 0.21) that may be explained by several factors including inbreeding, selfing and the Wahlund effect. In spite of a sampling design planned to avoid the sampling of clones, genotypically identical individuals for the six loci were found in some locations. The significance of these potential clones is discussed and their effect on the observed pattern of population structure assessed. Patterns of allelic distribution within populations suggest the possibility of a recent colonization of the Atlantic range from the Mediterranean Sea.

Bayesian inferences on the recent island colonization history by the bird Zosterops lateralis lateralis - A. Estoup; S. M. Clegg (Molecular Ecology, 2003)
The founding of new populations by small numbers of colonists has been considered a potentially important mechanism promoting evolutionary change in island populations. Colonizing species, such as members of the avian species complex Zosterops lateralis , have been used to support this idea. A large amount of background information on recent colonization history is available for one Zosterops subspecies, Z. lateralis lateralis , providing the opportunity to reconstruct the population dynamics of its colonization sequence. We used a Bayesian approach to combine historical and demographic information available on Z. l. lateralis with genotypic data from six microsatellite loci, and a rejection algorithm to make simultaneous inferences on the demographic parameters describing the recent colonization history of this subspecies in four southwest Pacific islands. Demographic models assuming mutation–drift equilibrium or a large number of founders were better supported than models assuming founder events for three of four recently colonized island populations. Posterior distributions of demographic parameters supported (i) a large stable effective population size of several thousands individuals with point estimates around 4000–5000; (ii) a founder event of very low intensity with a large effective number of founders around 150–200 individuals for each island in three of four islands, suggesting the colonization of those islands by one flock of large size or several flocks of average size; and (iii) a founder event of higher intensity on Norfolk Island with an effective number of founders around 20 individuals, suggesting colonization by a single flock of moderate size. Our inferences on demographic parameters, especially those on the number of founders, were relatively insensitive to the precise choice of prior distributions for microsatellite mutation processes and demographic parameters, suggesting that our analysis provides a robust description of the recent colonization history of the subspecies.

Queen-worker conflict over male production and the sex ratio in a facultatively polyandrous bumblebee, Bombus hypnorum: the consequences of nest usurpation - R. J. Paxton; P. A. Thoren; A. Estoup; J. Tengo (Molecular Ecology, 2001)

Queen–worker conflict over male production and the sex ratio in a facultatively polyandrous bumblebee, Bombus hypnorum : the consequences of nest usurpation - R. J. Paxton; P. A. Thorén; A. Estoup; J. Tengö (Molecular Ecology, 2001)
Evolutionary conflicts among social hymenopteran nestmates are theoretically likely to arise over the production of males and the sex ratio. Analysis of these conflicts has become an important focus of research into the role of kin selection in shaping social traits of hymenopteran colonies. We employ microsatellite analysis of nestmates of one social hymenopteran, the primitively eusocial and monogynous bumblebee Bombus hypnorum , to evaluate these conflicts. In our 14 study colonies, B. hypnorum queens mated between one and six times (arithmetic mean 2.5). One male generally predominated, fathering most of the offspring, thus the effective number of matings was substantially lower (1–3.13; harmonic mean 1.26). In addition, microsatellite analysis allowed the detection of alien workers, those who could not have been the offspring of the queen, in approximately half the colonies. Alien workers within the same colony were probably sisters. Polyandry and alien workers resulted in high variation among colonies in their sociogenetic organization. Genetic data were consistent with the view that all males ( n = 233 examined) were produced by a colony’s queen. Male parentage was therefore independent of the sociogenetic organization of the colony, suggesting that the queen, and not the workers, was in control of the laying of male‐destined eggs. The population‐wide sex ratio (fresh weight investment ratio) was weakly female biased. No evidence for colony‐level adaptive sex ratio biasing could be detected.

‘Neighbourhood’ size, dispersal and density estimates in the prickly forest skink ( Gnypetoscincus queenslandiae ) using individual genetic and demographic methods - J. Sumner; F. Rousset; A. Estoup; C. Moritz (Molecular Ecology, 2001)
Dispersal, or the amount of dispersion between an individual’s birthplace and that of its offspring, is of great importance in population biology, behavioural ecology and conservation, however, obtaining direct estimates from field data on natural populations can be problematic. The prickly forest skink, Gnypetoscincus queenslandiae , is a rainforest endemic skink from the wet tropics of Australia. Because of its log‐dwelling habits and lack of definite nesting sites, a demographic estimate of dispersal distance is difficult to obtain. Neighbourhood size, defined as 4π D σ 2 (where D is the population density and σ 2 the mean axial squared parent–offspring dispersal rate), dispersal and density were estimated directly and indirectly for this species using mark–recapture and microsatellite data, respectively, on lizards captured at a local geographical scale of 3 ha. Mark–recapture data gave a dispersal rate of 843 m 2 /generation (assuming a generation time of 6.5 years), a time‐scaled density of 13 635 individuals * generation/km 2 and, hence, a neighbourhood size of 144 individuals. A genetic method based on the multilocus (10 loci) microsatellite genotypes of individuals and their geographical location indicated that there is a significant isolation by distance pattern, and gave a neighbourhood size of 69 individuals, with a 95% confidence interval between 48 and 184. This translates into a dispersal rate of 404 m 2 /generation when using the mark–recapture density estimation, or an estimate of time‐scaled population density of 6520 individuals * generation/km 2 when using the mark–recapture dispersal rate estimate. The relationship between the two categories of neighbourhood size, dispersal and density estimates and reasons for any disparities are discussed.

Phylogeography and population structure of an ecotonal marsupial, Bettongia tropica , determined using mtDNA and microsatellites - L. C. Pope; A. Estoup; C. Moritz (Molecular Ecology, 2000)
The northern bettong, Bettongia tropica , is an endangered species of Potoroidae with a restricted distribution in the wet tropics of north Queensland, Australia. The species is only found within a thin strip of sclerophyll forest along the western margin of rainforest. This tight association with rainforest boundaries is predicted to have resulted in population isolation as rainforest contracted during the Pleistocene, though some have proposed that the northern bettong was not present in the wet tropics until the late Pleistocene. The dispersal ability of the species, and of the family, is not known. This study examined gene flow among populations within areas of continuous habitat complemented by a broader analysis of phylogeography. Individuals trapped at each of the four known regions (one region was subsampled at three different sites), were sequenced for 547 base pairs of the mitochondrial DNA (mtDNA) control region and typed for seven microsatellite loci. The mtDNA phylogeny showed congruence with a biogeographical hypothesis, a relatively deep split suggesting historical isolation in separate northern and southern refugia. The two divergent clades were both present within the Lamb Range, indicating an expansion from these refuges and subsequent admixture at one site. mtDNA allele frequencies indicated relatively limited gene flow within the Lamb Range over distances as short as nine km. Tests of population divergence using microsatellites ( F ST and assignment tests) strongly supported this result. A molecular signal indicative of a recent bottleneck was unexpectedly detected in one of the Lamb Range subpopulations. This lead us to examine the behaviour of the statistics used in this bottleneck test under a linear stepping‐stone model with varying migration rates. We found that it may be more difficult to detect molecular signatures for recent bottlenecks under conditions of very low migration rates than for isolated populations and, conversely, that ‘false’ bottleneck signatures may be observed at higher migration rates. The Lamb Range F ST estimate clearly fell within the category of potentially ‘false’ bottleneck signals. Despite relatively limited gene flow, evidence for asymmetric dispersal suggests more complicated population dynamics than a simple linear stepping‐stone model.

Juxtaposed microsatellite systems as diagnostic markers for admixture: an empirical evaluation with brown trout ( Salmo trutta ) as model organism - A. Estoup; C. R. Largiadèr; J.‐M. Cornuet; K. Gharbi; P. Presa; R. Guyomard (Molecular Ecology, 2000)
A juxtaposed microsatellite system (JMS) is composed of two microsatellite repeat arrays separated by a sequence of less than 200 bp and more than 20 bp. This paper presents the first empirical evaluation of JMSs for the study of genetic admixture induced by man, with brown trout ( Salmo trutta ) as model organism. Two distinct admixture situations were studied: native populations from streams of the Atlantic basin and of the Mediterranean basin, respectively, all stocked with domestic strains originating from the Atlantic basin. For these two situations, we first evaluated by simulation the ability of JMSs to differentiate between alien alleles and naturally shared homoplasious or ancestral alleles, and thus to behave as diagnostic markers for admixture. Simulations indicated that JMSs are expected to be reliable diagnostic markers in most divergent (i.e. Mediterranean) populations and nonreliable diagnostic markers in most closely related (i.e. Atlantic) populations. Three JMSs were genotyped in domestic strains as well as in nonstocked and stocked populations of brown trout sampled in different rivers of the Mediterranean and Atlantic basins. The observed distributions of JMS haplotypes were consistent with simulation predictions confirming that JMSs were reliable diagnostic markers only over a given proportion of the species range, i.e. in substantially divergent populations. JMSs also reinforced the diagnostic character of three microsatellite sites for the studied Mediterranean populations. This last result is consistent with our simulation results which showed that, although much less frequently than at JMSs, diagnostic markers are likely to be found at single site microsatellites provided that the native Mediterranean population has a sufficiently small effective population size. For each population of the Mediterranean basin admixture coefficients did not differ significantly across JMSs and mean admixture coefficients sometimes differ among populations. The interpretation of the origin of JMS haplotypes based on the allele length variants was supported by nucleotide sequence analysis.

Polymerase chain reaction primers for polymorphic microsatellite loci in the invasive toad species Bufo marinus - D. Tikel; D. Paetkau; M. N. Cortinas; R. Leblois; C. Moritz; A. Estoup (Molecular Ecology, 2000)

Isolation of microsatellite loci in European catfish, Silurus glanis - F. Krieg; A. Estoup; A. Triantafyllidis; R. Guyomard (Molecular Ecology, 1999)

Isolation and characterization of microsatellite markers in the nuclear genome of the brown alga Laminaria digitata (Phaeophyceae) - C. BILLOT; S. ROUSVOAL; A. ESTOUP; J. T. EPPLEN; P. SAUMITOU‐LAPRADE; M. VALERO; B. KLOAREG (Molecular Ecology, 1998)

Density and variability of dinucleotide microsatellites in the parthenogenetic polyploid snail Melanoides tuberculata - S. SAMADI; E. ARTIGUEBIELLE; A. ESTOUP; J.‐P. POINTIER; J.‐F. SILVAIN; J. HELLER; M.‐L. CARIOU; P. JARNE (Molecular Ecology, 1998)
Characterization of microsatellites in the parthenogenetic polyploid snail Melanoides tuberculata revealed an unusual high density of dinucleotide repeats. Multiple banding patterns were obtained at these loci, and interpreted as a consequence of polyploidy. Microsatellite variability was low within, but high between, shell morphotypes. Genotypes were wholly transmitted from mothers to offspring. These results suggest that reproduction is strictly apomictic, and that shell morphotypes are genetic clones.

Comparative analysis of microsatellite and allozyme markers: a case study investigating microgeographic differentiation in brown trout ( Salmo trutta ) - A. ESTOUP; F. ROUSSET; Y. MICHALAKIS; J.‐M. CORNUET; M. ADRIAMANGA; R. GUYOMARD (Molecular Ecology, 1998)

High degree of polyandry in Apis dorsata queens detected by DNA microsatellite variability - Robin F. A. Moritz; Per Kryger; Gudrun Koeniger; Nikolaus Koeniger; Arnaud Estoup; Salim Tingek (Behavioral Ecology and Sociobiology, 1995)